Differences in the sensitivity of ovarian cancer to photodynamic therapy and the mechanisms for those differences - Yokoyama, Yoshihito (Oncol Lett, 2017)
Protoporphyrin IX (PpIX) levels are crucial to the antitumor action of photodynamic therapy (PDT). In the present study, the underling molecular mechanisms for the variation in PpIX levels in ovarian cancer cells were investigated. Five ovarian cancer cell lines were subcutaneously grafted onto the backs of nude mice. Once tumors had developed, 5-aminolevulinic acid methyl ester hydrochloride (methyl-ALA) was administered intraperitoneally and the tumor was irradiated twice/week. PpIX levels in the tumor were assayed using high-performance liquid chromatography. Enzymes involved in heme synthesis and degradation were screened using a microarray technique. Expression of the glutathione transferase Omega-1 (GSTO1) gene involved in the conversion of PpIX into heme in cells was quantified using the reverse transcription-quantitative polymerase chain reaction. In HTOA, HRA and DISS cells, PDT resulted in significant tumor shrinkage in comparison with the controls. In MCAS and TOV21G cells, no significant alterations in tumor growth were identified compared with the untreated cells. PpIX levels increased significantly in HTOA, DISS and HRA cells compared with in MCAS and TOV21G cells. A comparison of genetic profiles using PDT-sensitive DISS cells and PDT-resistant MCAS cells indicated that MCAS cells exhibited significantly increased levels of δ-aminolevulinate synthase (a rate-limiting enzyme in heme synthesis), heme oxygenase 2 (an enzyme that degrades heme into biliverdin), and biliverdin reductase B (an enzyme that reduces biliverdin into bilirubin) in comparison with DISS cells. The level of GSTO1 expression in HTOA, HRA and DISS cells was ~2.5-fold that in MCAS and TOV21G cells. Sensitivity to PDT is related to PpIX levels in cells. The results of the present study suggested that PpIX tends not to accumulate in PDT-resistant cells despite active heme synthesis and degradation, and that high levels of GSTO1 expression are associated with increased sensitivity to PDT.